(untitled) (Economic Journal of Nepal, 2021)
This paper tries to analyze whether the ‘Political Business Cycle (PBC)’ exists in Nepal or not. The term PBC is coined to describe the fluctuation in economic activities from the intervention of the political actors before the election expecting to be re-elected in the forthcoming election. The abuse of political power in manipulating fiscal and monetary policies by the ruling party prior to the election period has become normal in developing countries like Nepal. The incumbent tries to convince their voters by increasing the size of the populist public expenditure before or during the election period. Nepal can’t be exceptional in the case of public resource manipulation during the time of the election. Democracy was restored in Nepal after the people’s political movement of 1990 and after that six consequent general elections were completed. The study used the annual data set from 1990/91 to 2017/18 and employed the ordinary least square method in three different models to capture the relationship among the variables used in the study. Real GDP, government consumption expenditure, and fiscal deficit are used as dependent variables of each model whereas government capital expenditure, transfer payment and subsidy, and total tax revenue are taken as independent variables under the study along with introducing election as a dummy variable. The results showed a positive relationship between the variables, but not enough to confirm the opportunistic political business cycle. The study recommends policymakers ensure policy consistency considering non-intervention in fiscal policies at the time of election.